Research on bifurcation and chaos characteristics of planet gear transmission system with thermal deformation - Jingyue Wang; Zhijian Wu; Haotian Wang; Jianming Ding; Cai Yi (Journal of Low Frequency Noise, Vibration and Active Control)
A computational model is proposed for the calculation of thermal deformation in ring gear, and the ANSYS Workbench platform is utilized to simulate the steady-state temperature field and thermal deformation in a planetary gear system. The simulation results are utilized to validate the accuracy of the ring gear thermal deformation calculation model. Furthermore, based on the data obtained from the steady-state temperature field, this research investigates variations in gear backlash and coupling stiffness within planetary gear systems caused by thermal deformation under variable speed and torque conditions. Additionally, a nonlinear dynamic model incorporating thermal deformation factors is established for a planetary gear system. By employing the 4-5 order Runge-Kutta numerical method, bifurcation diagrams and Largest Lyapunov exponents of the system under different operating conditions are obtained. Combining Poincaré maps, phase diagram, and spectral diagrams, an analysis is conducted on tooth impact states as well as nonlinear dynamic characteristics of the system influenced by thermal deformation.